Deletion analysis of the 51-kilodalton protein of the Bacillus sphaericus 2362 binary mosquitocidal toxin: construction of derivatives equivalent to the larva-processed toxin. - Clark, M A (1990)
Bacillus sphaericus 2362 produces a binary toxin consisting of 51- and 42-kDa proteins, both of which are required for toxicity to mosquito larvae. Upon ingestion by larvae, these proteins are processed to 43 and 39 kDa, respectively. Using site-directed mutagenesis, we have obtained N- and C-terminal deletions of the 51-kDa protein and expressed them in B. subtilis by using the subtilisin promoter. Removal of 21 amino acids from the N terminus and 53 amino acids from the C terminus resulted in a protein with the same electrophoretic properties as the 43-kDa degradation product which accumulates in the guts of mosquito larvae. This protein was toxic only in the presence of the 42-kDa protein. A deletion of 32 amino acids at the N terminus combined with a 53-amino-acid deletion at the C terminus resulted in a protein which retained toxicity. Toxicity was lost upon a further deletion of amino acids at potential chymotrypsin sites (41 at the N terminus, 61 at the C terminus). Comparison of the processing of the 51- and the 42-kDa proteins indicated that in spite of their sequence similarity proteolysis occurred at different sites.